Religiosity, spirituality, and mental health in Portugal: a call for a conceptualisation, relationship, and guidelines for integration (a theoretical review) - Freire, J.; Moleiro, C. (Psicologia, 2015)
In the Portuguese research society, particularly in the mental health field, little has been done regarding religiosity, spirituality and mental health. Thus, this paper strives to stimulate the interest in this area by providing an overview of the body of research on religiosity, spirituality and mental health, highlighting the role and importance these dimensions represent in the life of many people, whether in health or mental distress and illness. A brief review of the conceptualisation of religion (religiosity) and spirituality is provided, as well as some areas of disagreement and contention. Guidelines for the integration and professional training are also included, not discarding the ethical considerations inherent in this process. Finally, reflections are offered as to why bringing religiosity and spirituality into mental health field is important, as well as some implications for clinical practice, with particular focus on Portuguese mental health system